Personality traits and cognitive ability in political selection - Markus Jokela; Jaakko Meriläinen; Janne Tukiainen; Åsa von Schoultz (Aboa Centre for Economics (ACE), 2023)
We present the first comprehensive evidence on the role of cognitive ability and personality traits in the selection of electoral candidates and election of politicians. Using unique data that combine population registers and election statistics from local government elections in Finland with tests of cognitive and non-cognitive ability of men administered by the Finnish Defense Forces, we document two main findings. First, political parties select candidates who fare better than the office-eligible population in both intelligence and personality tests that capture three dimensions of cognitive and seven dimensions of non-cognitive ability. Second, elected politicians possess more desirable traits than nonelected candidates. Our results show that a voter-oriented open-list system is able to select competent, motivated, and honest representatives. We also assess the relative importance of cognitive abilities and personality traits, present evidence of no trade-offs between politician quality and descriptive representation, and illustrate that political competition may be an important contextual factor shaping selection.
Keywords: D72; J24; 330; candidate entry; cognitive ability; election; open-list PRsystem; personality; political selection